An Overview on Cystic Fibrosis - Swetha Reddy Singireddy1, Swetha Reddy; Varagandhi, Susmitha; Jagiri, Aishwarya Goud; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Cystic fibrosis is an autosomal recessive disease. It is caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene on chromosome 7 that codes for a protein transmembrane conductance regulator (CFTR) protein which functions as a transmembrane cAMP-activated chloride channel. CFTR also affects other ion channels, most notably blocking the influx of sodium into the cell through the epithelial sodium channel. The CFTR abnormality has been shown to produce a number of changes in the airway, including acidification and decreased water and ion transit. A pulmonary exacerbation of CF is usually identified by an increase in cough and sputum and a decrease in pulmonary function. Disease manifests in many organs, but most notably the upper and lower airways, pancreas, bowel, and reproductive tracts. Pulmonary function testing is a major tool for evaluating and monitoring disease state and progression in CF. Spirometry is the commonly used pulmonary function test. Management of CF requires good nutrition and appropriate supplementation of vitamins and pancreatic enzymes. The Cystic Fibrosis Foundation recommends the following treatments as having a high certainty of substantial net benefit, grade A, for moderate-to-severe disease: inhaled tobramycin, dornasealfa, ivacaftor, and inhaled aztreonam. Preventing or treating intestinal blockages—oral rehydration and osmotic laxatives (incomplete blockage) and hyperosmolar contrast enemas (complete DIOS). Antibiotics are the major components of CF treatment and are administered chronically (e.g. inhaled antibiotics, macrolides used for their immunomodulatory properties) or intermittently to prevent, eradicate, control or treat respiratory infections. Lumacaftor (200 mg) + ivacaftor (125 mg), Orkambi, is the first approved CFTR corrector and potentiator combination therapy. Keywords: